THE BEHAVIORIAL PHENOMENON OF FRIEND WITH BENEFIT OF ALTER BASE @FWBSMG ON TWITTER - Muhammad Faruq Bukhori (Jurnal Ilmiah Global Education, 2023)
The emergence of alter ego accounts on Twitter triggers a new phenomenon called "friend with benefit," known as FWB. This phenomenon arises because there is a place to share information and communicate with each other. This FWB behavior is mushrooming on social media with an alter ego account, a second account aimed at seeking FWB, and a means of more unrestrained self-expression. This study aims to describe the FWB phenomenon, identify the forms of FWB behavior, and determine how the alter ego's motives account for FWB behavior. The method used in this research is qualitative content analysis with a qualitative approach. The method obtained is based on observations of @FWBSmg tweet content, interviews, and document review. The results of this study indicate that the FWB phenomenon carried out by alter ego accounts on Twitter is carried out because they want to find satisfaction both sexually and emotionally. Not only that but FWB is also conducted to find friends to chat and hang out with. The results of this study also show that the alter ego account is used as a second account to search for FWB and that the pattern used by the alter ego in searching for FWB on Twitter is also supported by the alter base community named @FWBSmg. Alter ego accounts send menfess with the gender terms "M" for male and "F" for a female when looking for FWB. They are also sending menfess photos by covering their faces with stickers; which is done to hide their real identities in public.